2008
DOI: 10.1186/1472-6793-8-12
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training improves relaxation response and SOD-1 expression in aortic and mesenteric rings from high caloric diet-fed rats

Abstract: BackgroundObesity has been associated with a variety of disease such as type II diabetes mellitus, arterial hypertension and atherosclerosis. Evidences have shown that exercise training promotes beneficial effects on these disorders, but the underlying mechanisms are not fully understood. The aim of this study was to investigate whether physical preconditioning prevents the deleterious effect of high caloric diet in vascular reactivity of rat aortic and mesenteric rings.MethodsMale Wistar rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(77 citation statements)
references
References 46 publications
9
60
1
7
Order By: Relevance
“…These data suggest that the HFD+F induced vascular dysfunction which was not related to damage or disturbances in the smooth muscle intracellular response since endothelium independent relaxation was not affected by the treatment and morphological changes were not seen as well. This finding confirms previous studies that showed reduced endotheliumdependent relaxation without changes in the endothelium-independent relaxation in another model of rat obesity and other models of risk factors for cardiovascular disease such as arterial hypertension and diabetes [19][20][21][22]. Together with the morphological analysis of the mesenteric artery showing that the intima and medium layers were preserved in HFD+F group, it is suggestive that the impaired endothelium-dependent relaxation in the HFD+F group was not associated with damage in the endothelial layer.…”
Section: Citationsupporting
confidence: 79%
“…These data suggest that the HFD+F induced vascular dysfunction which was not related to damage or disturbances in the smooth muscle intracellular response since endothelium independent relaxation was not affected by the treatment and morphological changes were not seen as well. This finding confirms previous studies that showed reduced endotheliumdependent relaxation without changes in the endothelium-independent relaxation in another model of rat obesity and other models of risk factors for cardiovascular disease such as arterial hypertension and diabetes [19][20][21][22]. Together with the morphological analysis of the mesenteric artery showing that the intima and medium layers were preserved in HFD+F group, it is suggestive that the impaired endothelium-dependent relaxation in the HFD+F group was not associated with damage in the endothelial layer.…”
Section: Citationsupporting
confidence: 79%
“…In addition, the obese rats developed metabolic disorders such as glucose intolerance, hyperinsulinemia and hyperleptinemia, characteristics commonly related to human obesity 15,19,20 . Insulin-resistance, defined as decreased sensitivity and/or responsiveness to metabolic actions of insulin, is a cardinal feature of diabetes, obesity and dyslipidemia 21 .…”
Section: Time (Min)mentioning
confidence: 99%
“…Esse fato nos chamou a atenção, pois o grupo HT teve valores significativamente maiores no CT e LDL, menor valor na HDL e maior PRF. Com isso, sugere-se que o treinamento pode ter influenciado a formação e progressão da placa, pois estudos demonstraram que o exercício físico aeróbico melhora os sistemas de defesa orgânicos contra aterosclerose, diminuindo o estresse oxidativo e aumentando a síntese de enzimas antioxidantes, aumentando a vasodilatação dos vasos sanguíneos via óxido nítrico (NO) e óxido nítrico sintase endotelial (eNOS) e diminuindo a inflamação sistêmica pela diminuição da produção de citocinas pró-inflamatórias e aumento de fatores anti-inflamatórios [34][35][36] . Estudos têm sido feitos para a comprovação dos efeitos benéficos do exercício físico aeróbico na redução e prevenção de doenças cardiovasculares (DC) 2,34,37 .…”
Section: Discussionunclassified